Preclinical Imaging: an Essential Ally in Modern Biosciences - Cunha, Lídia (2014)
Translational research is changing the practice of modern medicine and the way in which health problems are approached and solved. The use of small-animal models in basic and preclinical sciences is a major keystone for these kinds of research and development strategies, representing a bridge between discoveries at the molecular level and clinical implementation in diagnostics and/or therapeutics. The development of high-resolution in vivo imaging technologies provides a unique opportunity for studying disease in real time, in a quantitative way, at the molecular level, along with the ability to repeatedly and non-invasively monitor disease progression or response to treatment. The greatest advantages of preclinical imaging techniques include the reduction of biological variability and the opportunity to acquire, in continuity, an impressive amount of unique information (without interfering with the biological process under study) in distinct forms, repeated or modulated as needed, along with the substantial reduction in the number of animals required for a particular study, fully complying with 3R (Replacement, Reduction and Refinement) policies. The most suitable modalities for small-animal in vivo imaging applications are based on nuclear medicine techniques (essentially, positron emission tomography [PET] and single photon emission computed tomography [SPECT]), optical imaging (OI), computed tomography (CT), magnetic resonance imaging (MRI), magnetic resonance spectroscopy imaging (MRSI), and ultrasound. Each modality has intrinsic advantages and limitations. More recently, aiming to overcome the inherent limitations of each imaging modality, multimodality devices designed to provide complementary information upon the pathophysiological process under study have gained popularity. The combination of high-resolution modalities, like micro-CT or micro-MRI, with highly sensitive techniques providing functional information, such as micro-PET or micro-SPECT, will continue to broaden the horizons of research in such key areas as infection, oncology, cardiology, and neurology, contributing not only to the understanding of the underlying mechanisms of disease, but also providing efficient and unique tools for evaluating new chemical entities and candidate drugs. The added value of small-animal imaging techniques has driven their increasing use by pharmaceutical companies, contract research organizations, and research institutions.